The role of motivation in eating disorders: understanding sex differences in the circuits - Nasini, Sofia; Casile, Antonino; Bonaldo, Brigitta; Mancini, Camilla; Guzzo, Serafina Manila; Botticelli, Luca; Comai, Stefano (Frontiers in Behavioral Neuroscience, 2025)
Motivated behaviors, such as reproduction and feeding, are essential for mammalian survival. Although these behaviors serve distinct evolutionary purposes, they share a common function: fulfilling specific biological needs. Their regulation involves distinct brain regions and is influenced by a complex interplay of neural circuits, with significant sex-based differences. Alterations in motivation represent critical components of effort-based decision-making processes in eating disorders (EDs). Importantly, the impairments in motivated behavior observed in EDs arise not from structural changes within the relevant brain regions but rather from functional alterations influenced primarily by gonadal hormones. These hormones play a pivotal role in the pathophysiology of EDs, driving sex-based differences in both the qualitative aspects of symptom presentation and developmental trajectories through intracellular genomic signaling pathways. The current review examines sex differences in motivated behavior within the context of EDs.